Karakteristik Minyak Ikan Manyung (Arius sp.) dengan Metode Dry Rendering - Adam Ade Wijaya; Stephanie Bija; Ira Maya Abdiani (Universitas Sriwijaya, 2023)
Manyung fish (Arius sp.) is a demersal species that lives in sea and estuary waters. In Tarakan City, North Kalimantan, the meat of Manyung fish is widely consumed by the society, but the liver is discarded. One of the efforts to utilize manyung fish liver, so it does not become waste was prepare it into fish oil products. The aims of this study were to determine the yield of manyung fish (Arius sp.) liver oil, test its chemical characteristics, such as free fatty acid value (FFA), peroxide value (PV), and fatty acid profile. The method used for producing manyung fish (Arius sp.) liver oil is extraction by dry rendering at 80°C for 2 hours. The data obtained from the results of the research were then processed in a quantitative descriptive manner. The results showed that the fat content of manyung fish liver was 3.60%. The yield of manyung fish (Arius sp.) was 14.25%. The free fatty acid values (FFA) were 14.60%. The peroxide value was 3.46 mEq/kg. The fatty acid profile of mayung fish liver oil (Arius sp.) in dry rendering, the content of SFA was 0.0344%, MUFA was 0.022%, and PUFA was 0.184%. The conclusion of this research is manyung fish liver can be produced into fish oil.